State Analysis of the Shaft Bearing Force Based on the Full Model Harmonic Reducer - Wang Xinlong; Pang Xiaoxu; Qiu Ming; Yang Gengsheng; Zhu Dingkang (Jixie chuandong)
For the force problem of the flexible thin-walled bearing in harmonic reducers, the inadequacy of the previous single-factor analysis of the bearing is analyzed； and in order to explore the influence of other components on the bearing force of the shaft, theoretical analysis is conducted through the whole machine model, the deformation of the flexible wheel and the coordination process of the raceway roller deformation are explored, and the force state of the thin-walled flexible bearing is obtained as a whole. By verifying the stress and deformation of the whole machine model by Workbench software, the results show that the force state of the bearing simulation is consistent with the theoretical calculation.